Does Innovation Matter? Evidence from Enterprise Survey of ASEAN Countries - Muhammad Fuad; Shresta Purnamasari; Muhammad Sofian Maksar (Universitas Negeri Semarang, 2023)
This study embarks on an investigation to unearth evidence that innovation may, in certain contexts, fail to foster enterprise development. Innovation has been identified as a key driver of firms’ growth. However, to have successful innovation requires some minimum capabilities and resources. Based on this notion, we tried to find evidence that innovation may fail to help enterprises develop. The study use the World Bank's enterprise survey. The survey collected samples from ASEAN firms. Respondents were chosen by using stratified random sampling technique based on the type of business for all small, medium and large non-agricultural companies in all geographical areas. We used instrumental variable regression to avoid simultaneous causality. The findings show that while innovation has a considerable impact on the growth of non-SMEs, it has little or no impact on SMEs. This confirms our prediction that innovation dampen firms’ development, particularly those with limited abilities to innovate successfully. The research emphasizing the importance of tailored approaches to accommodate the diverse landscape of businesses, particularly in the dynamic ASEAN market.